Support for "Normalization" of Relations Between Palestinians and Israelis, and how It Relates to Contact and Resistance in the West Bank - Mai Albzour; Sandra Penic; Randa Nasser; Eva G. T. Green (Journal of Social and Political Psychology, 2019)
Since the launching of the Oslo peace process in 1993, the term ‘normalization’ has been used to characterize policies that aim to recognize the state of Israel and to establish ‘normal’ relations between Israelis and Palestinians. Whereas the Palestinian Authority has been supportive of normalization policies, numerous domestic and international critics have argued that these policies serve to perpetuate occupation and its consequences. We examine how Palestinians understand normalization, to what degree they support various forms of ‘normalizing’ relations with Israelis, and how contact with Israelis relates to support for normalization and motivation for revolutionary resistance against the occupation. Based on a cross-sectional survey conducted among an adult sample (N = 159) in the West Bank in 2016, we show that the understanding of normalization was multi-faceted, and that support for contact and collaboration across group lines (i.e., with Israelis) depended on the type of intergroup relations. On average, respondents were more supportive of relations within the political sphere, e.g. civilian policies and diplomatic coordination, than of interpersonal contact, cultural cooperation or security coordination. Support for most types of intergroup relations was related to decreased motivation for revolutionary resistance. In line with research on ‘sedative’ effects of positive intergroup contact in historically unequal societies, we found that past positive contact with Israelis was linked to decrease in Palestinians’ motivation for revolutionary resistance through increased support for interpersonal contact and security coordination as forms of normalization.